Minat Belajar Siswa Sekolah Dasar Berdasarkan Orientasi Kognitif - Laesti Nurishlah; Siti Nur Sholihah; Mochammad Ramdan Samadi (STAI Al-Mas'udiyah, 2023)
Interest in learning among elementary school students is crucial for academic success. Learning interest can be influenced by factors such as teaching approaches, classroom environment, and types of media used for instruction. This study aims to investigate the relationship between elementary school students' learning interest and their cognitive orientation. Using a literature review method, this research discusses the importance of understanding individual differences in students' learning and explores how students' cognitive orientations, such as task orientation and ego orientation, affect their learning interest. The results indicate that students with task orientation tend to be more interested in problem-solving and conceptual understanding, while students with ego orientation may require external incentives to motivate learning. The practical implications of these findings underscore the importance of using teaching strategies aligned with students' cognitive orientations, developing supportive classroom environments, and providing feedback that reinforces task orientation while reducing ego orientation.